Histopathological and molecular confirmation of Porcine Cystic Echinococcosis (CE)/Hydatidosis in Nepal - Joshi, DD; Yamasaki, H (Journal of Institute of Medicine Nepal, 2011)
Introduction: Cystic echinococcosis/hydatidosis is a cyclo-anthropozoonotic disease (parasitic infestation) of herbivorous animals and human caused by larval stage of Echinococcus tapeworm, belonging to the family Taeniidae. Dogs and some wild carnivores like foxes are definitive hosts harbouring worms in their intestine while herbivorous animals and man are intermediate host. Human acts as the dead-end host of the parasite. It is known that cystic echinococcosis in humans and pigs is prevalent in Nepal. Methods: This study was carried out in Kathmandu valley pig rearing areas. Two cysts found in the pig pancreas were examined by histopathology and molecular analysis. Results: In the histopathological examination, the laminated layers of the cystic walls were strongly stained with PAS, and protoscoleces were observed in the cyst. In the present study, it was first confirmed that two hydatid cysts found in pigs were identified as Echinococcus granulosus sensu stricto (sheep strain, E. granulosus G1) by mitochondrial DNA analysis. Conclusions: Molecular analysis is indispensable not only for studying Echinococcus species associated with pathogenicity and clinical manifestation, but also for molecular epidemiology. Keywords: Echinococcosis; Echinococcus granulosus sensu stricto; sheep strain; histopathology; mitochondrial DNA analysis DOI: http://dx.doi.org/10.3126/joim.v32i3.4961 Journal of Institute of Medicine, December, 2010; 32:3 54-58